Kontribusi Pemikiran Syaikh Abdul Wahab Rokan Dalam Bidang Pendidikan Agama Islam Di Kabupaten Langkat - Kamaliah, Muhammad Saleh, Ahmad Fuadi (Khazanah : Journal of Islamic Studies, 2023)
From the results of observations made by the author at the research location, information was obtained that the concept of Shaykh Abdul Wahab Rokan's thought in the field of Islamic religious education was through the concept of thought in the field of Sufism and the establishment of the Naqsabandiyah tariqat in Besilam. The results of these observations were developed into research formulations about the contribution of Shaykh Abdul Wahab Rokan's thought in Langkat. The purpose of this study was to determine the influence of the contribution of Sheikh Abdul Wahab Rokan's thought in the field of Islamic Agaranlitema Education in Langkat. The research method used is qualitative research through data collection techniques based on observations, interviews and documentation. After conducting interviews with informants, it was concluded that Shaykh Abdul Wahab Rokan's role in supporting the development of Islamic religious education in Langkat was as follows: The establishment of the Azizi mosque as a means for Muslims to carry out fardhu prayers and as a place of recitation from the master teacher, royal mufti in preaching so that da'wah communication can run effectively. Place of Education in the form of building Madrasah Jam'iyah Mahmudiyah. Naqsabandiyah Order in Basilam. The development of Islamic religious education during the time of Shaykh Abdul Wahab Rokan, namely that it had developed rapidly, namely the construction of madrasa buildings that were used for the process of managing education, teachers in charge of teaching also received facilities from the sultanate of Langkag so that the process of implementing Islamic religious education was carried out by the Shaykh Abdul Wahab Rokan with a style of modernization education approach so that the implementation of education in madrasas does not only run traditionally in the form of learning and teaching in the Koran house, the house of suluk but religious education adopts a teaching style among the Dutch colonialists but the use of the curriculum still maintains an Arabic School-based religious education curriculum.